2024
DOI: 10.1002/advs.202305515
|View full text |Cite
|
Sign up to set email alerts
|

Axial Phenoxylation of Aluminum Phthalocyanines for Improved Cannabinoid Sensitivity in OTFT Sensors

Halynne R. Lamontagne,
Rosemary R. Cranston,
Zachary J. Comeau
et al.

Abstract: Cannabis producers, consumers, and regulators need fast, accurate, point‐of‐use sensors to detect Δ9‐tetrahydrocannabinol (THC) and cannabidiol (CBD) from both liquid and vapor source samples, and phthalocyanine‐based organic thin‐film transistors (OTFTs) provide a cost‐effective solution. Chloro aluminum phthalocyanine (Cl‐AlPc) has emerged as a promising material due to its unique coordinating interactions with cannabinoids, allowing for superior sensitivity. This work explores the molecular engineering of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
(140 reference statements)
0
6
0
Order By: Relevance
“…In all cases, the phenoxy-AlPcs led to a reduction in OTFT performance, but an improvement in sensing response. AFM, XRD, UV–vis, and GIWAXS all demonstrated that the phenoxy-AlPcs exhibited greater changes in molecular structure and in some cases the appearance of new polymorphs were observed upon exposure to THC and CBD . We surmised that the phenoxy groups lead to additional possible interactions between the semiconductor and the THC and CBD, and a reduction in intermolecular AlPc interactions, leading to more significant changes in morphology, upon exposure, as observed.…”
Section: Optimization Of Otft Cannabinoid Sensorsmentioning
confidence: 53%
See 3 more Smart Citations
“…In all cases, the phenoxy-AlPcs led to a reduction in OTFT performance, but an improvement in sensing response. AFM, XRD, UV–vis, and GIWAXS all demonstrated that the phenoxy-AlPcs exhibited greater changes in molecular structure and in some cases the appearance of new polymorphs were observed upon exposure to THC and CBD . We surmised that the phenoxy groups lead to additional possible interactions between the semiconductor and the THC and CBD, and a reduction in intermolecular AlPc interactions, leading to more significant changes in morphology, upon exposure, as observed.…”
Section: Optimization Of Otft Cannabinoid Sensorsmentioning
confidence: 53%
“…AFM, XRD, UV−vis, and GIWAXS all demonstrated that the phenoxy-AlPcs exhibited greater changes in molecular structure and in some cases the appearance of new polymorphs were observed upon exposure to THC and CBD. 49 We surmised that the phenoxy groups lead to additional possible interactions between the semiconductor and the THC and CBD, and a reduction in intermolecular AlPc interactions, leading to more significant changes in morphology, upon exposure, as observed. This study demonstrated that simple modifications of the MPc semiconductor can be an effective way to improve OTFT sensors sensitivity.…”
Section: ■ Optimization Of Otft Cannabinoid Sensorsmentioning
confidence: 71%
See 2 more Smart Citations
“…22 The use of organic semiconductors can also introduce unique interactions and sensing mechanisms to analytes such as the specific film restructuring of phthalocyanines with exposure to cannabinoids. [23][24][25][26][27] To date, the majority of reported OTFT sensors rely on manual deposition of analyte solutions, typically using micropipettes. 28,29 Though manual droplet dispensing can be convenient for single devices, it is not a scalable process for high-throughput testing, prevents continuous analysis, and has been shown to introduce significant run-to-run variation, limiting reproducibility.…”
Section: Introductionmentioning
confidence: 99%